(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In the article, one of the changes occurring in the translation process stylistic change, is discussed in detail during the analysis of “Everything, everything” by Nicola Yoon. Below are some examples of stylistic change to better understand this type of change.